Gastronomia e imigração alemã na região central do Rio Grande do Sul: colônia de Santo Ângelo (segunda metade do século XIX) - Friedrich, Fabiana Helma (2015)
This dissertation is part of the Research Line "Culture, Migration and Work" Area of Concentration in History, Power and Culture on History Postgraduate Program at Federal University of Santa Maria, which received funding from CAPES. Food and Culinary of German immigrants - between the mid-nineteenth century and early twentieth century - were not simply transplanted. Food products hitherto unknown, had to be taken availed of, transforming tastes and flavors, resulting in a regional and original immigrant culinary. The main interest of this research is to understand how was the process of identity construction of German immigrants in the central region of Rio Grande do Sul, considering the social and cultural practices of the alimentation and its implications for society as a reinforcing element of an identity and immigrant memory in the new continent. Primary sources and research literature brought information about the behaviors and feeding practices of the group chosen for the research in question.